Kemampuan Pemecahan Masalah Matematis Ditinjau Berdasarkan Kecerdasan Emosional Siswa Kelas VII SMP - Fransiska Meni Oeleu; Samuel Igo Leton; Aloysius Joakim Fernandez (Asimtot : Jurnal Kependidikan Matematika, 2019)
The research aims to get an overview about the ability of students in solving mathematical problem based on their emotional intelligence. This is qualitative research with a case study design. The subjects of this research were seventh-grade students who has high emotional intelligence, consisting of a student from catholik junior high school in Kefamenanu and one students from state secondary school in Kota Kupang, They were obtained using purposive. The data were collected using a questionnaire of emotional intelligence, a mathematical problem-solving task, and a interview sheet. The analysis of what is obtained from both subjects, being the high crossing of catholik junior high school students Kefamenanu, it is obtained from cross-leg’s ability: students can understand the matter, make quick plans, to implement completion plans and examine back. The state junior high school in Kupang have the ability of low-vang problems acquired from abilities of emerging problems: students cannot understand matter, students are less able to create completion plans and students cannot examine the return settlement sequences